2019
DOI: 10.1038/s41398-019-0495-5
|View full text |Cite
|
Sign up to set email alerts
|

Spaced training improves learning in Ts65Dn and Ube3a mouse models of intellectual disabilities

Abstract: Benefits of distributed learning strategies have been extensively described in the human literature, but minimally investigated in intellectual disability syndromes. We tested the hypothesis that training trials spaced apart in time could improve learning in two distinct genetic mouse models of neurodevelopmental disorders characterized by intellectual impairments. As compared to training with massed trials, spaced training significantly improved learning in both the Ts65Dn trisomy mouse model of Down syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 168 publications
6
9
0
Order By: Relevance
“…Latencies at day 10 were in the range of 20 sec in Ube3a mice trained with distributed learning trials, spaced at 1 h intervals, as compared with latencies at day 10 in the range of 30-35 sec, in Ube3a mice trained with massed learning trials (Fig. 2), consistent with previous findings (Lauterborn et al 2019). No significant difference was detected in the time course across training days for acquisition by Ube3a mice treated with vehicle versus 7,8-DHF (F (1,19) = 0.07, NS), indicating no faster learning with 7,8-DHF.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Latencies at day 10 were in the range of 20 sec in Ube3a mice trained with distributed learning trials, spaced at 1 h intervals, as compared with latencies at day 10 in the range of 30-35 sec, in Ube3a mice trained with massed learning trials (Fig. 2), consistent with previous findings (Lauterborn et al 2019). No significant difference was detected in the time course across training days for acquisition by Ube3a mice treated with vehicle versus 7,8-DHF (F (1,19) = 0.07, NS), indicating no faster learning with 7,8-DHF.…”
Section: Resultssupporting
confidence: 91%
“…(B) Ube3a in both the vehicle and 7,8-DHF groups did not successfully reach the acquisition criterion of under 15 sec to reach the hidden platform location, although acquisition latencies at day 10 were generally lower after spaced training trials than latencies at day 10 after the massed training trials shown in Figure 2. This observation extends previous findings of better learning with spaced versus massed training in 2to 3-mo-old Ube3a mice (Lauterborn et al 2019). No significant difference was detected in the time course across training days for acquisition by Ube3a mice treated with vehicle versus 7,8-DHF.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations